2012
DOI: 10.1038/pcan.2011.70
|View full text |Cite
|
Sign up to set email alerts
|

Assessing prostate cancer growth with citrate measured by intact tissue proton magnetic resonance spectroscopy

Abstract: BACKGROUND Annual PSA tests have led to a significant increase in the number of prostate cancer (PCa) cases diagnosed. This increased incidence has led to overtreatment of many patients, as current pathology often cannot distinguish latent from aggressive PCa. Studies have shown that the depletion of zinc in prostate cells correlated with cell-line growth rates, and may therefore relate to the progression of PCa. Furthermore, as zinc is normally an inhibitor of citrate oxidation, the reduction of zinc in PCa m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 35 publications
2
13
1
Order By: Relevance
“…A decrease in Cit concentrations in benign epithelia was correlated to faster PCa growth rates ( p < 0.05, n = 27 from 18 patients), as low Cit/epithelia levels were symptomatic of rapid increase in PSA values ( r 2 = 0.27, p < 0.034), and hence higher PSA velocities. Similar results were reported when correlating Cit/epithelia with PSA densities ( r 2 = 0.31, p < 0.021) and blood percent‐free PSA ( r 2 = 0.53, p < 0.011) …”
Section: Applications Of Hrmas Mrs In Studies Of Human Malignant Disesupporting
confidence: 83%
See 1 more Smart Citation
“…A decrease in Cit concentrations in benign epithelia was correlated to faster PCa growth rates ( p < 0.05, n = 27 from 18 patients), as low Cit/epithelia levels were symptomatic of rapid increase in PSA values ( r 2 = 0.27, p < 0.034), and hence higher PSA velocities. Similar results were reported when correlating Cit/epithelia with PSA densities ( r 2 = 0.31, p < 0.021) and blood percent‐free PSA ( r 2 = 0.53, p < 0.011) …”
Section: Applications Of Hrmas Mrs In Studies Of Human Malignant Disesupporting
confidence: 83%
“…In addition, Cit and Spm were also linearly correlated ( r 2 = 0.75, p = 0.0001). The reduction of Cit is likely due to the depletion of zinc in PCa cells, since zinc can function to prevent oxidation of Cit in the Krebs' cycle . Spm is also an important metabolite in the prostate for its inhibitory effect on the growth of PCa cells in vitro .…”
Section: Applications Of Hrmas Mrs In Studies Of Human Malignant Disementioning
confidence: 99%
“…5 Metabolomics is defined as a global quantitative analysis of all endogenous metabolites in a biological system such as an organ, tissue or body fluid. However, despite these discrepancies, the report of Sreekumar et al, 8 together with other studies, [9][10][11][12][13][14][15] suggests it is worth using single metabolites or metabolite patterns for diagnostic or prognostic purposes in patients suffering from prostate cancer. 5 Since metabolite profiles closely reflect the total cellular situation, metabolomics has been developed into a more integrative approach in comparison with the other omic approaches.…”
mentioning
confidence: 99%
“…While metabolomic profiles have been shown to provide an enhanced capacity in the diagnosis and monitoring of PCa, there are many findings from studies focusing on individual metabolites in prostate tissue using HRMAS that have proven very valuable in advancing our understanding of PCa. The metabolites spermine, a polyamine abundant in the prostate and a proposed endogenous inhibitor of PCa growth [28], and citrate, a critical prostate metabolite related to zinc depletion in malignant prostate tissue [29], have both been found to correlate with the volume percentage of histologically benign prostatic epithelial cells, while the latter also correlated with PSA velocity, PSA density, and serum percent free PSA [30]. Other studies found phosphocholine, taurine, myo-inositol, scyllo-inositol, lactate, and alanine concentrations to be significantly higher, and ethanolamine concentrations, significantly lower, in PCa tissue compared with benign tissue [3133].…”
Section: Pca Metabolomicsmentioning
confidence: 99%